Kuktem's hands-on goal - UMP, . (The New Straits Times Press (M) Berhad, 2002)
WITH the goal of producing highly-skilled manpower to enhance the country's economic growth, Kolej Universiti Kejuruteraan dan Teknologi Malaysia (Kuktem), a university college, has begun operations in Kuantan since early this year.